Architectures of survival : air war and urbanism in Britain, 1935-52 - Page, Adam (Manchester University Press, 2018)
Architectures of survival investigates how airpower influenced urbanism and debates about the future of cities in modern Britain. It traces the targeting of cities and militarisation of urban space from interwar to Cold War and highlights how air raids became incorporated into civilian planning debates about cities and infrastructure.